The impact of social commerce determinants on social capital for energy sectors - Shanmugam M.; Gheni A.Y.; Fadhil bin Yusof A.; Karunakaran V. (University of Tehran, 2023)
This study investigates the constructs and related theories that drive social capital in energy sector from the intention perspectives. This research uses theories of 'social support' and 'planned behaviour' alongside satisfaction and perceived value to propose a research model that drives social capital for energy sectors in Malaysia. The model reveals that the Theories of Planned Behaviour (TPB) and Social Support Theory (SST) alongside satisfaction and perceived value factors promote social capital development in energy sectors. Using PLS-SEM to analyse data gathered from energy sector employees in Malaysia, this research demonstrates that social capital is present when there is trust and loyalty among the users and positively effects energy sectors in terms of the productivity, effectiveness, efficiency and profitability. The study also contributes to the understanding of individuals' use of social capital in energy sector. A survey is adapted and distributed to 100 respondents as a mean to study on the validity and reliability of the research factors. Results indicate that all seven hypotheses proposed significantly influence social capital. University of Tehran, Faculty of Management